2014
DOI: 10.7150/ijms.8182
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Bone Marrow-Derived Cells Transplantation in MPTP-rat Model of Parkinson's Disease: A Comparison Study of Mononuclear and Mesenchymal Stem Cells

Abstract: The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) animal model is a useful tool to study Parkinson's disease (PD) and was used in the present study to investigate the potential beneficial as well as deleterious effects of systemic bone-marrow mononuclear cell (BMMC) or mesenchymal stem cell (BM-MSC) transplantation. MPTP administration resulted in a breakdown of the blood-brain barrier and motor impairment in the open field test 24 h after surgery. Three and 7 days after receiving the lesion, the injured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 65 publications
0
17
0
1
Order By: Relevance
“…It was previously reported that naïve, neurotrophic factorsecreting, or neurally induced MSCs have therapeutic effects when transplanted into 6-OHDA-or MPTP-induced Parkinsonian animals (Biju et al, 2013;Capitelli et al, 2014;Dezawa et al, 2004;Glavaski-Joksimovic et al, 2010;McCoy et al, 2008;Park et al, 2014;Sadan et al, 2009;Wang et al, 2013;Weiss et al, 2006;Yan et al, 2013). A beneficial effect of the striatal transplantation of both SHEDs and DAergic neuronlike SHEDs was also previously reported (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…It was previously reported that naïve, neurotrophic factorsecreting, or neurally induced MSCs have therapeutic effects when transplanted into 6-OHDA-or MPTP-induced Parkinsonian animals (Biju et al, 2013;Capitelli et al, 2014;Dezawa et al, 2004;Glavaski-Joksimovic et al, 2010;McCoy et al, 2008;Park et al, 2014;Sadan et al, 2009;Wang et al, 2013;Weiss et al, 2006;Yan et al, 2013). A beneficial effect of the striatal transplantation of both SHEDs and DAergic neuronlike SHEDs was also previously reported (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…There were 20 experiments conducted to evaluate rotational behavior and 8 experiments conducted to evaluate limb function. In addition, there were three studies using the rotarod test [36,81,83] and three studies using the open field test [80,84,89]. Because of insufficient numbers, these studies on rotarod and open field were not included in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 96%
“…Recently, bone marrow MSCs (BM-MSCs) have been reported to have the potential to develop into neural lineages such as those for neurons, astrocytes, and oligodendrocytes both in vivo (Eglitis and Mezey 1997;Kopen et al 1999, Lee et al 2013Capitelli et al 2014) and in vitro (SanchezRamos et al 2000;Woodbury et al 2000;Deng et al 2001). Some attempts to use MSCs for the treatment of CNS disorders have even been reported (Chopp et al 2000;Kang et al 2003;Joyce et al 2010;Momin et al 2010).…”
Section: Introductionmentioning
confidence: 96%